Meat Preservation with Addition of Kecombrang Leaves (Etlingera Elatior) in Refrigerator Temperature - Kusuma, Citra; Rusman, Rusman; Jamhari, Jamhari (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2017)
The purpose of this study was to determine the effect of kecombrang leaves (Etlingera elatior) on the physical, chemical and microbiological quality on meat that stored at refrigerator temperatures. The research was conducted in June until August 2016 in the Laboratory of Meat Science and Technology Department of Product Technology, Faculty of Animal Science, Gadjah Mada University. This study used a completely randomized design (CRD) 3 x 3 factorial (3 condition of kecombrang leaves, 3 storage time), each treatment was repeated 3 times, and the different means were tested by Duncan test. The results Showed that the addition of kecombrang leaves and storage time had significantly affected (P<0.05) on the total microbes in meat. Meat control (8,00 log cfu/ml±0,48) and meat with the addition of kecombrang leaves powder (6,59 log cfu/ml±0,40) more effective in suppressing of total microbes that growing compared with kecombrang leaves pasta (7,12 log cfu/ml±0,35). Storage time make pH value and cooking losses in meat decrease. Kecombrang leaves condition and storage time did not affected to water content, protein content, fat content and tenderness in beef.